Crisis within a crisis. Psychological dimension of the pandemic - Markiewicz, Renata (Polish Journal of Public Health, 2020)
The COVID-19 pandemic caused chaos in many countries. The reason of that were mostly lack of knowledge concerning the disease, fear of infection, difficulties in defining its consequences. A reasonable action in fighting the epidemic turned out to be social isolation and suspension of all state institutions. While at the beginning of introduction of those actions the society accepted the restrictions with understanding, the prolonging state of isolation caused in some people increased anxiety, fear and concerns about the future. Reduction of a negative effect of pandemic can be a problem for a long time, especially when we will not be able to adequately interpret a danger, comprehend it and appropriately react. Crisis within a crisis. Psychological dimension of the pandemic